The Anthropometric Profiles and Physical Fitness for Elementary School Children (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2021)
The aim of this study was to determine the anthropometric profile data and physical fitness of elementary school children aged 10-12 years 11 Tanjung Batu public elementary school 2020-2021. The method used in this research is quantitative descriptive method by measuring and testing TKJI 2010, the total sample is 25 students. The results of the research obtained on the anthropometric profile to see the body mass index obtained the nutritional status of 18 underweight students, 7 normal people, on the physical fitness test, 5 people were in good category, 16 people were enough, and 4 people were enough, and there was a relationship between anthropometric profiles. with students' physical fitness. After the data has been obtained, the teachers at the 11 Tanjung Batu public elementrary school can review and make a reference in the upcoming learning process, so that anthropometric data and the level of student’s physical fitness can improve from before and will be even better.